Biomarkers of treatment response in patients with progressive multiple sclerosis treated with high‐dose pharmaceutical‐grade biotin (MD1003). Issue 2 (13th December 2020) - Collongues, Nicolas; Kuhle, Jens; Tsagkas, Charidimos; Lamy, Julien; Meyer, Nicolas; Barro, Christian; Parmar, Katrin; Amann, Michael; Wuerfel, Jens; Kappos, Ludwig; Moreau, Thibault; de Seze, Jerome
Abstract: Background: High‐dose pharmaceutical‐grade biotin (MD1003) has positive effects on disability in progressive multiple sclerosis (PMS), but its mechanism of action remains unclear. The objective of our study was to quantify the effect of MD1003 in patients with PMS, using clinical response, plasma neurofilament light chain (pNfL) levels, and brain (BV) or cervical spinal cord volume (CSCV). Materials and methods: Forty‐eight patients with PMS newly treated with MD1003 were followed during one year. Patients were assessed clinically using the Expanded Disability Status Scale (EDSS), the nine‐hole peg test (9HPT), and the 25‐foot walk time (25FWT). CSCV was quantified using CORDIAL software and BV using SIENA or SIENAX. We measured pNfL level using SIMOA at several time points. Bayesian linear and logistic regressions were used to evaluate potential prognostic factors. Results: Treatment response, defined as a significant decrease of EDSS, 25FWT, or 9HPT at 1 year, was observed in 13 patients (27%). A gain of volume was noted in 7/24 patients for brain and in 10/19 patients for cervical spinal cord. The strongest predictors of poor treatment response were a high pNfL level at MD1003 onset (OR 0.96; 95% CI [0.91; 1]), high age at MS onset (OR 0.95; 95% CI [0.89; 1.01]), and an increase in brain lesion load during MD1003 treatment (OR 0.81; 95% CI [0.55; 1.05]). Conclusions: MD1003 treatment was associated with clinical, BV, and CSCV improvement at 1 year. The correlation between the levels of pNfL at baseline, the age at multiple sclerosis onset, and a treatment response at M12 is consistent with a better effect in less disabled patients. Abstract : MD1003 treatment was associated with clinical, brain and cervical spinal cord volumes improvement at 1 year. The correlation between the levels of pNfL at baseline, the age at MS onset and a treatment response at M12 is consistent with a better effect in less disabled patients. Our study provides a set of objective assessments that, taken together, argue for a possible neuroprotective or remyelinating effect of MD1003 in progressive forms of MS.